Effect of polycystic ovary syndrome on dysmenorrhea: a case-control study - Behzadfar, Samaneh; Jalilvand, Faranak; Salehi, Narges (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Polycystic ovary syndrome (PCOS) is a common endocrine disorder that has an important impact on women of reproductive age and is diagnosed with various hormonal disorders. Menstrual pain is a common and often problematic problem for women during their reproductive age. Although these two problems may appear to be presented separately, they often overlap and lead to complex and multiple challenges in health care for women. This study was conducted with the aim of the effect of PCOS on dysmenorrhea. Methods: This case-control study was done on 92 women who visited Alavi hospital in Ardabil during 2022-2023. Data collected included age, body mass index, length of the menstrual cycle (in days), menstrual bleeding volume (number of pad changes during the menstrual cycle), duration of menstrual bleeding (in days), and the presence of menstrual pain. Additionally, the severity of menstrual pain was assessed using the visual analog scale (VAS). Data were analyzed using SPSS version 25. Results: Mann-Whitney test showed a significant difference between subjects with PCOS and non-PCOS in terms of the frequency of pain scores (p=0.03). There was no significant difference between the two groups in the variable of pain intensity (p=0.70). Conclusions: The results of this study showed that the frequency of dysmenorrhea increases in people with PCOS, but the intensity of menstrual pain does not increase.